1H‐NMR and GC for detection of adulteration in commercial essential oils of Cymbopogon ssp. Issue 1 (29th July 2019) - Cerceau, Cristiane I.; Barbosa, Luiz C.A.; Alvarenga, Elson S.; Maltha, Celia R.A.; Ismail, Fyaz M.D.
Abstract: Introduction: Essential oils of Cymbopogon nardus and C . winterianus have fungicidal, bactericidal, and insect repellent activities. In addition, they are components of fragrances, cosmetics, and household products. The growing demand for essential oils has intensified adulteration practices of such products. Objectives: To evaluate the authenticity and quality of citronella commercial essential oils based on chemical composition [by gas chromatography mass spectrometry (GC‐MS)] and the contents of its major constituents [by 1 H‐NMR, and gas chromatography with a flame ionisation detector using internal standardisation (GC‐IS)]. Materials and Methods: The chemical composition of essential oil was determined by GC‐MS. Major components were quantified by 1 H‐NMR and the results compared to those obtained by GC‐IS. Results: The adulteration of oils was verified by GC and 1 H‐NMR. In the pure oils, the results obtained by 1 H‐NMR were similar to those obtained by GC‐IS for most of the oils. However, in adulterated oils, signal overlap prevented the quantification of citronellol and geraniol by NMR. Importantly, due to dilution with dipropylene glycol it was not possible to quantify citronellal using 1 H‐NMR. However, for both pure and adulterated oils, GC‐IS method proved successful in quantifying notable constituents. Conclusion: All the methods used proved efficient in detecting adulteration. However, whilst GC‐IS provided quantification of constituents of interest, both in pure and adulterated oils, their quantification by NMR was only possible in non‐adulterated samples. None of the oils evaluated presented a composition within the threshold established by British Pharmacopoeia quality standards. Abstract : This work evaluated the quality of citronella commercial essential oils based on chemical composition (GC‐MS) and the contents of its major constituents by quantitative 1 H‐NMR, and gaschromatography using internal standardization (GC‐IS). All the methods proved efficient in detecting adulteration. However, whilst GC‐IS provided quantification of constituents of interest, bothin pure and adulterated oils, their quantification by NMR was only possible in non‐adulterated samples. None of the oils presented a composition within thethreshold established by British Pharmacopoeia.